Development of a fish oil–nanoemulsion gel as a drug-delivery system to prevent capsular contracture - Mohuya Paul; Sang Gue Kang; Jungkyun Im; Woo Jin Song (Scientific Reports)
Abstract Capsular contracture, a significant complication of breast-implant surgery, causes pain and deformation following the formation of a tight capsule around an implant. Current surgical and non-surgical treatment options are invasive, expensive, and typically administered for prolonged periods, potentially leading to side effects. To address these challenges, we developed a novel fish oil-encapsulated, poloxamer-based nanoemulsion gel with omega-3 (ω3) as the primary active component (NE-ω3 gel; N3G). This formulation can be injected during surgery, reducing the need for prolonged administration of medications and minimizing associated side effects. N3G was prepared through a two-step process involving the emulsification of fish oil followed by gelation with poloxamer to create a thermoreversible gel. Dynamic light-scattering analysis confirmed a uniform distribution of nanoemulsion particles, which had a mean diameter of 287 ± 8.599 nm and a PDI of 0.29 ± 0.047. FTIR and DSC analyses validated the encapsulation of fish oil within poloxamer micelles. Drug-release analysis demonstrated that more than 96% of fish oil was released within 10 h. In in vivo experiments, rats (n = 30) were divided into three groups: a negative control group (G1), a positive control group receiving fish oil (G2), and an experimental group with implants coated with N3G (G3). G3 exhibited a 21.2% reduction in capsular thickness compared to G1 and a 5.6% reduction compared to G2. In addition, significant decreases in fibrosis and myofibroblast counts were observed in G3. These results, supported by histological and gene expression analyses, highlight the effectiveness of N3G in reducing inflammation and fibrosis. This study underscores the therapeutic potential of N3G for capsular contracture, based on its persistence, thermoreversibility, and improved dosing and storage characteristics.